Demerits of Remdesivir: An Unseen Trouble (Bangladesh Journal of Infectious Diseases, 2020)
Remdesivir is an investigational antiviral agent available for COVID-19 therapy. Even though its efficacy has been proven through various clinical trials, the evidence is still scarce. The side effects of remdesivir are highlighted in this paper and should be kept in mind during its use. Moreover, the availability of this drug is limited, and we fear an impending shortage of the said medicine in the near future. Thus through this letter we hope to increase awareness regarding this potentially lifesaving medicine.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S67-S68